The Role of Sociology of Law in Promoting Social Order: A Socio-Legal Perspective - Muh. Sabir; Mukhlis Achmad; Ahmad Fadli; Marzuki Irham (Journal AGENCY, 2026)
The sociology of law provides an interdisciplinary framework for understanding how legal norms interact with social values, institutions, and human behavior in shaping social order. Despite the existence of comprehensive legal regulations, many societies continue to experience low legal compliance, social conflicts, and inconsistent law enforcement, indicating that legal effectiveness depends not only on normative validity but also on social acceptance. This study aims to examine the role of the sociology of law in promoting social order by analyzing the relationship between legal awareness, legal culture, and the implementation of state law within diverse social contexts. The research employs a normative legal method complemented by a socio-legal approach through the analysis of legislation, legal doctrines, and relevant scholarly literature. The findings demonstrate that social order is more likely to be achieved when legal norms are formulated and enforced in accordance with prevailing social values, cultural traditions, and community expectations. The sociology of law contributes to improving legal effectiveness by strengthening public legal awareness, fostering trust in legal institutions, and integrating state law with living law practiced within society. Furthermore, the study reveals that legal compliance is influenced by the quality of law enforcement, public participation, legal education, and the legitimacy of legal institutions. It concludes that a socio-legal perspective is essential for developing responsive legal policies capable of balancing legal certainty with social justice. Integrating sociological insights into lawmaking and enforcement can enhance legal legitimacy, encourage voluntary compliance, and promote sustainable social order in democratic and pluralistic societies.